2018
DOI: 10.2144/btn-2018-0039
|View full text |Cite
|
Sign up to set email alerts
|

Luciferase Complementation Based-Detection of G-Protein-Coupled Receptor Activity

Abstract: Protein complementation assays (PCA) are used as pharmacological tools, enabling a wide array of applications, ranging from studies of protein-protein interactions to second messenger effects. Methods to detect activities of G protein-coupled receptors (GPCRs) have particular relevance for drug screening. Recent development of an engineered luciferase NanoLuc created the possibility of generating a novel PCA, which in turn could open a new avenue for developing drug screening assays. Here we identified a novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…1 , A and B ). This site was similar but not identical to another NanoLuc split site used previously in a direct-recruitment assay ( 21 ).
Figure 1 Validation of a novel NanoLuc split for use in complementation-based assays.
…”
Section: Resultssupporting
confidence: 51%
“…1 , A and B ). This site was similar but not identical to another NanoLuc split site used previously in a direct-recruitment assay ( 21 ).
Figure 1 Validation of a novel NanoLuc split for use in complementation-based assays.
…”
Section: Resultssupporting
confidence: 51%
“…The GLuc-emitted luminescence was already sufficiently detectable in the presence of 5 μM coelenterazine; therefore, this concentration was used in the experiments. Similar to previous reports ( 17 , 18 ), we found that NanoLuc efficiently utilizes some other coelenterazine derivatives as well, such as 2-deoxycoelenterazine (coelenterazine h ). Although coelenterazine h was shown to be inferior as a substrate of NanoLuc compared with furimazine, it still induced sufficient brightness to perform BRET measurements in our setup.…”
Section: Resultssupporting
confidence: 91%
“…NanoBiT has provided the opportunity to measure GPCR–effector interactions in real time in living cells with a high degree of sensitivity. 25,26,31,32 Here, we have used the high-affinity HiBiT tag to detect cell surface expression of the adenosine A 1 receptor and quantified the loss of receptors at the cell surface in response to agonist treatment as a measure of receptor internalization.…”
Section: Discussionmentioning
confidence: 99%